Studies on mononuclear chelates derived from substituted Schiff-base ligands (Part 2): Synthesis and characterization of a new 5-bromosalicyliden-p-Aminoacetophenoneoxime and its complexes with Co(II), Ni(II), Cu(II) and Zn(II) - Canpolat, E; Kaya, M (Taylor & Francis Ltd, 2004)
In this study, 5-broniosalicyliden-p-aminoacetophenoneoxime (LH) was synthesized starting from p-amino-acetophenoneoxime and 5-bromosalicylaldehyde. Complexes of this ligand with Co+2, Ni+2, Cu+2 and Zn+2 were prepared with a metal: ligand ratio of 1 : 2. Their structures have been elucidated on the basis of elemental analyses, IR, H-1 and C-13 NMR spectra, electronic spectra, magnetic susceptibility measurements. molar conductivity and thermogravimetric analyses (TGA).
Keywords: Schiff bases; transition metal complexes